(untitled) (TERRA LATINOAMERICANA, 2023)
Maize is an important cereal in terms of human and animal nutrition worldwide. In our study, the bacterial microbiome composition of the soil rhizosphere was compared among three maize (Zea mays L.) races: forage (C1), dual-purpose (C2) and grain (C3). Additionally, the impact of the bacterial microbiome of the soil rhizosphere over yield was determined. Our study was conducted in plots located in the El Retiro Experimental Field at Universidad Autónoma Agraria Antonio Narro (UAAAN). Soil sampling was carried out in June 13, 2021, 51 days af ter sowing. DNA was extracted from three samples of each maize race. The V3-V4 region of the 16S rRNA gene was amplified and massive next-generation sequencing was performed with Illumina. The bioinformatic analysis was conducted in QIIME using the bacterial taxonomic reference of EzBioCloud. The phylum Proteobacteria, the class Phycisphaerae, the orders Shingomonadales, Micrococcales and Phycisphaerales, the families Moroxellaceae, Micrococcaceae, Chitinophagaceae, Shingobacteriaceae and Enterobacteriaceae, as well as the genera Acinetobacter, Shingobacterium and Cryseobacterium, were the bacterial taxa that dif fered in relative abundance among the three races (P < 0.05, Kruskal-Wallis test and an average dissimilarity > 0.10 in the SIMPER analysis). Among the taxa identified, plant growth promoting bacteria (PGPB) such as Acinetobacter and Sphingobacterium were detected. The race C2 showed the best yields of grain weight (15.56 Mg ha-1) and forage dry weight (10.61 Mg ha-1). Thus, we conclude that C2 represents a good option to preserve the seed and that further research should be developed for this race under dif ferent conditions.